Perception about self-medication practices for oral health problems among the general population of Davangere city, Karnataka, India - Anjan Giriraju (Wolters Kluwer Medknow Publications, 2014)
Background: Self-medication is a widely accepted practice in many developing countries. The determining factors of self-medication need to be first understood to develop appropriate medicine information policies and patient-provider education strategies. Keeping this in mind, present survey was conducted with the aim to assess the perception about self-medication practices for oral health problems among the general population of Davangere city, Karnataka, India. Materials and Methods: A cross-sectional field survey was conducted among 440 subjects in Davangere city. Data were collected through a specially designed proforma using a closed-ended, self-administered questionnaire containing 12 questions, in three sections. Results: Response rate of the survey was 100%. Self-medication and nondoctor prescription was found to be obvious and at an alarming rate of 70.9%. Among reasons of self-medication, toothache was the most common one. People of all sociodemographic categories approved self-medication giving reasons of lack of time as a major reason followed by nonseriousness of their condition. Analgesics, herbal remedies were often used for treating their oral health problems. Most of the respondents consulted pharmacist for basic treatment and only decided to approach a dentist if the problem persisted. Majority of respondents were aware of the adverse effect regarding the drug prescribed including expiry date of the medication used. Conclusions: Self-medication for oral health problems prevalence was higher in the population of Davangere city. Pharmacists and family influence played a major role in self-medication for oral health problems.